Legal Regulation of Biotechnology Use: Certain Perspectives for Legislative Reform - Omelchenko , Olha (Actual problems of law (Aktual'ni problemi pravoznavstva), 2026)
From year to year, the value of the global biotechnology market is growing, which is associated with a number of factors, including the expansion of the areas of use of biotechnology (from agriculture, the food industry to medicine, pharmacy and even the fashion industry). At the same time, the legal regulation of biotechnology is fragmentary both at the level of national legislation and at the level of international legislation. The article analyzes the current legislation on the legal regulation of the use of biotechnology through the prism of the prospects for its reform and reform of the legislation of the European Union.The research methodology is based on a complex combination of several methods. The comparative method is used to study the use of legal terminology, a doctrinal analysis of modern scientific literature is carried out, and individual legislative provisions are studied using the analysis and synthesis method.The progress of the use of biotechnology in medicine and pharmacy requires the formation of an appropriate legal framework. The draft Civil Code of Ukraine (Code of Private Law) No. 14394 of 22.01.2026 in Article 308 proposes to enshrine the right of an individual to bodily integrity, including with regard to making decisions on biotechnological interventions. The EU is currently working on adopting a Regulation on establishing a framework of measures for strengthening Union’s biotechnology and biomanufacturing sectors particularly in the area of health, which will aim to strengthen the EU's competitiveness in the field of pharmaceuticals by removing regulatory barriers and creating an environment with uniform standards for clinical trials. In the context of legal protection of intellectual property rights for biotechnological inventions, the legal framework should contribute to achieving a balance between stimulating research, developing innovation and ensuring public interests in the field of health.